2021
DOI: 10.3390/diagnostics12010081
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of the Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) in Various Respiratory Diseases: A Retrospective Analysis

Abstract: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte (PLR) ratio are two extensively used inflammatory markers that have been proved very useful in evaluating inflammation in several diseases. The present article aimed to investigate if they have any value in distinguishing among various respiratory disorders. One hundred and forty-five patients with coronavirus disease 2019 (COVID-19), 219 patients with different chronic respiratory diseases (interstitial lung disease, obstructive sleep apnea(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…NLR and PLR can reveal systemic inflammatory responses, which are conducive to an increase in neutrophils and platelets and a decrease in lymphocytes, making their ratios a valuable tool for indirect assessment of inflammatory status and cellular immunity ( 42 ) in a variety of diseases, such as malignancies (including hematological malignancies), respiratory infections, gastrointestinal diseases, cardiovascular and cerebrovascular diseases (such as acute coronary syndrome, cerebral hemorrhage), systemic diseases (diabetes mellitus, diabetic foot) and, most recently, COVID-19. Patients with the above illnesses showed higher PLR and/or NLP than normal controls ( 43 49 ). More research data have indicated that during the COVID-19 pandemic, hospitalized positive cases with sleep disorders presented lower absolute lymphocyte counts and higher NLRs than those without sleeping problems ( 50 ).…”
Section: Discussionmentioning
confidence: 93%
“…NLR and PLR can reveal systemic inflammatory responses, which are conducive to an increase in neutrophils and platelets and a decrease in lymphocytes, making their ratios a valuable tool for indirect assessment of inflammatory status and cellular immunity ( 42 ) in a variety of diseases, such as malignancies (including hematological malignancies), respiratory infections, gastrointestinal diseases, cardiovascular and cerebrovascular diseases (such as acute coronary syndrome, cerebral hemorrhage), systemic diseases (diabetes mellitus, diabetic foot) and, most recently, COVID-19. Patients with the above illnesses showed higher PLR and/or NLP than normal controls ( 43 49 ). More research data have indicated that during the COVID-19 pandemic, hospitalized positive cases with sleep disorders presented lower absolute lymphocyte counts and higher NLRs than those without sleeping problems ( 50 ).…”
Section: Discussionmentioning
confidence: 93%
“…Hypoxemia, more than inflammation, seems to have a stronger impact on PLR, which has a better discriminative value in patients with OSA or chronic obstructive pulmonary disease (COPD). A recent report showed that PLR is a poor, but significant predictor for OSA-COPD [ 27 ]. Another study documented a significant association between AHI and PLR and revealed that a PLR value beyond 159 is independently associated with the presence of hypertension in OSA patients [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…These readily available inflammatory biomarkers have potential prognostic implications in malignancies [ 20 , 21 ], autoimmune [ 22 ], respiratory [ 23 ] and cardiovascular disease [ 24 , 25 , 26 ]. PLR seems to be more influenced by hypoxemia and has recently proved to be a poor, but significant predictor for OSA-COPD [ 27 ]. Larger platelets seem to have a prothrombotic phenotype and are associated with increased cardiovascular risk [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and oxidative stress are known to play a key role in COPD pathogenesis [50]. Neutrophils and macrophages are the main innate immune cells that infiltrate the lungs and participate in the pathogenesis of CS-induced COPD through inflammation and direct induction of endothelial and epithelial cell death [20,51,52]. Neutrophils have been detected to be increased in the small airways of COPD patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have been detected to be increased in the small airways of COPD patients [53]. Inflammatory alveolar macrophages tend to express inflammatory cytokines and secrete matrix metalloproteases, and activated neutrophils are recruited to the airways and release reactive oxygen species (ROS) and neutrophil elastase, causing an injury to the epithelium and underlying basement membrane in the lung tissues and leading to COPD progression [20,51,52,54]. Such inflammatory cells can also promote immune responses, leading to an elevation in levels of inflammatory cytokines, which intensify the inflammatory response and exert a key role in the airway inflammation in COPD by recruiting inflammatory cells and airway hyper-responsiveness [55][56][57][58][59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%